Is Dynamic Condylar Screw Better Than (95°) Blade Plate in Management of Subtrochanteric Fracture of Femur? (Iraqi Journal of Medical Sciences, 2020)
Background: Subtrochanteric fractures account for approximately 10-30% of all hip fractures, affecting persons of all ages and should be internally fixed to reduce the morbidity and mortality by early rehabilitation and mobilization. A dynamic condylar screw (DCS) and a 95° angle blade plate (BP) provide a good choice for fixation of subtrochanteric fractures so it is a matter of debate that which one is the best fixation in such fractures.Objective: To evaluate the surgical treatment of subtrochanteric fracture of femur using DCS versus a 95° BP.Methods: Prospective comparative study of 40 patients conducted in Al-Imamein Al-Kadhimein Medical City from November 2015 to November 2017. Twenty patients treated with open reduction and internal fixation by using DCS and other twenty patients treated with open reduction and internal fixation by using a 95° BP. The mode of injury, site and type of fracture, age of patients, operating time, and blood loss, union rate, complication of implants, functional results were compared between the groups. Results: Out of 40 patients, there were 26 (65%) male, right side affected in 24 (60%) patients. Mechanism of injury was trivial trauma observed in 28 (70%) patients. According to a Russell-Taylors classification, majority of fractures are type IB that observed in 16 (40%) patients. Majority of the patients, 27 (67.5%), started full weight bearing at 14 weeks. There was no significant mean age difference between the two groups (p=0.7). The mean operation time of DCS (83±4.3 min) was lower significantly than of 95° BP (p
Keywords: Subtrochanteric fractures of femur; dynamic condylar screw; 95 BP